2018
DOI: 10.1080/02643944.2018.1453858
|View full text |Cite
|
Sign up to set email alerts
|

What does research tell high school teachers about student motivation for test performance?

Abstract: Motivation' is a significant concept for teachers and students during programmes of learning which lead explicitly to high stakes assessments and examinations. This systematic literature review surveys current research evidence to find out how secondary school teachers use motivational strategies specifically in respect of student academic assessment and performance.Six research studies were identified describing the behaviours secondary school teachers engaged in to improve student performance in assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…The result was not consistent with some previously reported works, who argued that prior knowledge influence basic-learning skill scores (James et al, 2008;Lambić & Lipkovski, 2012;Lin & Liou, 2019;Mutodi & Ngirande, 2014;Reinholz & Gillingham, 2017;Richardson et al, 2012). Meanwhile other authors (Fernández & Figueiras, 2014;Flitcroft & Woods, 2018;H. C. Hill et al, 2004;Hollingsworth & Knight-McKenna, 2018;Kizito et al, 2016;Remillard, 2005;Schlomer, 2017;Tachie & Molepo, 2019) revealed the other variables that impact basic-learning skill scores in mathematics, including students' workload, teachers' knowledge, curriculum, and pedagogy.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The result was not consistent with some previously reported works, who argued that prior knowledge influence basic-learning skill scores (James et al, 2008;Lambić & Lipkovski, 2012;Lin & Liou, 2019;Mutodi & Ngirande, 2014;Reinholz & Gillingham, 2017;Richardson et al, 2012). Meanwhile other authors (Fernández & Figueiras, 2014;Flitcroft & Woods, 2018;H. C. Hill et al, 2004;Hollingsworth & Knight-McKenna, 2018;Kizito et al, 2016;Remillard, 2005;Schlomer, 2017;Tachie & Molepo, 2019) revealed the other variables that impact basic-learning skill scores in mathematics, including students' workload, teachers' knowledge, curriculum, and pedagogy.…”
Section: Discussioncontrasting
confidence: 68%
“…The higher levels of mathematical knowledge (H. C. Hill, Schilling, & Ball, 2004;Schlomer, 2017) showed a greater focus on student mathematical thinking, meanwhile, limited mathematics thinking impact a smooth transition into mathematics programs (Hourigan & Leavy, 2017). Flitcroft and Woods (2018) revealed that teacher behaviors to students' academic performance have both positive and negative impacts, according to their positive or negative attitude, and King and Cattlin (2015) found that there are significant negative impacts associated with students' pass rates with large numbers of students enrolling in degrees. Hence, there is evidence of positive relationship between prior knowledge, mathematics preferences, qualification, workload, higher levels of mathematical knowledge, as well as teacher behaviors and mathematics learning.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…With the motivation to learn, students will be increasingly interested in being involved in the learning process (Ambrosi-randi & Ruži, 2010;Vero & Puka, 2017;Wood, Rowell, & Hong, 2013). A student with high learning motivation tends to achieve learning success (Flitcroft & Woods, 2018;Wood et al, 2013). In fact, some researchers claim that motivation acts as one of the main keys to one's academic success (Hoffman, 2009;Joibari & Mohammadtaheri, 2011;Mohzan, Hassan, & Halil, 2013;Sogunro, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative investigations utilised a framework previously used by Flitcroft and Woods (2018), and Woodley-Hume and Woods (2019), and based on research appraisal guidelines (Genaidy et al, 2007;Wallace and Wray, 2011). These were coded with final scores assigned up to 16 points, with criteria including clear research question or hypothesis, multi-level or intergroup analyses, limitations of the research and implications of findings.…”
Section: Methodsmentioning
confidence: 99%